2018
DOI: 10.1002/ppul.23978
|View full text |Cite
|
Sign up to set email alerts
|

Outcome evaluation of a pharmacy‐based therapy management program for patients with cystic fibrosis

Abstract: ObjectiveTo compare medication adherence, pulmonary exacerbations, healthcare utilization, and costs for patients with cystic fibrosis (CF) who utilized a pharmacy‐based therapy management program to a matched control group. We hypothesized that patient management services would be associated with better medication adherence, and thus require fewer visits to the emergency room or hospitalizations.MethodsThis retrospective, observational cohort study used claims data from the MORE2 claims Registry®. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…Published literature has demonstrated that improving access for people to obtain medications has positive health outcomes . Anstead et al showed that by having patients fill CF medications at a single health‐system‐based specialty pharmacy affiliated with the CF clinic, patient medication access improved by 98%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Published literature has demonstrated that improving access for people to obtain medications has positive health outcomes . Anstead et al showed that by having patients fill CF medications at a single health‐system‐based specialty pharmacy affiliated with the CF clinic, patient medication access improved by 98%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in multidisciplinary care model, pharmacists and respiratory therapists may work together to provide tailored patient education about various respiratory medications. The finding of higher percentage of respondents reporting emergency department visits in clinics with pharmacist involvement is more perplexing as the study by Kirkham et al showed a decrease in emergency room utilization occurred in CF patients managed by a pharmacy program. One possible explanation for the increase in emergency room utilization in clinics with pharmacist involvement is patients experiencing pulmonary exacerbation may reach out to their more accessible CF clinic pharmacists for direction, and in collaboration with the CF multidisciplinary healthcare team, advise them to seek care at the emergency department …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several outpatient clinics and hospitals have also developed their own internal specialty pharmacies to improve communication with providers, streamline access to care, provide a source of revenue, and ultimately deliver more consistent care to patients by involving pharmacy professionals. Such services have been shown to increase adherence with dornase alfa (Pulmozyme; Genentech, South San Francisco, CA) and inhaled tobramycin; however, data are lacking for other cystic fibrosis (CF) medications, which have their own unique complexities . The University of Iowa Hospitals and Clinics (UIHC) established an internal specialty pharmacy in August 2013 that was accredited in November 2016 by the Utilization Review Accreditation Commission and the Joint Commission.…”
Section: Introductionmentioning
confidence: 99%